Relationship Coagulation Indicator with Hyperglycemia and Hyperlipidemia in Diabetes Mellitus Disease: Hubungan Indikator Koagulasi dengan Hiperglikemia dan Hiperlipidemia pada Penyakit Diabetes Melitus - Wisam Abdan Wawi AL Abdullah (Academia Open, 2025)
Metabolism dysfunction including hyperglycemia and hyperlipidemia in diabetes mellitus case are crucial factors in developing vascular diseases, platelet activation and hypercoagutable state. Increasing coagulation factors and hypercoagulability were reported in diabetes mellitus patients which due to increase of coagulation factors that resulted in prothrombotic state and extension of thrombolytic lysis in diabetes patients. Thus, this works amid to exam the association between coagulation index's with hyperglycemia and dyslipidemia in diabetes mellitus patients. FBG, HbA1c, PT, APTT, INR, D-dimer, platelets and MPV values were showed significant increase in diabetic's patients compared with their levels of healthy. Lipids profiles, AIP and TC/HDL ratio were found significantly higher in patients they were suffering from diabetic. Person correlation analysis presented a strong association between prothrombin time and (FBG, PLT, TC and LDL). MPV and AIP were a moderate positive correlate with prothrombin time. Prothrombin time was a weak correlated with HbA1c, TG, HDL and TC/HDL ratio. However, D-dimer and VLDL were negatively associated with prothrombin time. APTT value presented a strong positive association with FBG and LDL, a moderate positive relationship with AIP and TC/HLD. There was a weak positive association between APTT value HbA1c, D-dimer, PLT, MPV, TC and HDL. However, TG and VLDL were negatively correlated with APTT value. Highlights: Metabolic Dysfunction: Hyperglycemia and dyslipidemia increase coagulation factors in diabetes. Key Findings: Significant rise in PT, APTT, D-dimer, lipid profiles, and MPV. Correlations: Prothrombin time associates strongly with FBG, PLT, TC, and LDL. Keywords: diabetes, Prothrombin time, activated partial thromboplastin, atherogenic index of plasma, coagulation factors